1992
DOI: 10.1016/0014-5793(92)80256-g
|View full text |Cite
|
Sign up to set email alerts
|

Serum calcium‐decreasing factor (caldecrin) from porcine pancreas has proteolytic activity which has no clear connection with the calcium decrease

Abstract: WC purified a grurtl calcium-decreasing factor, which showed chymotrypsin.;ikc proteasc activity, from porcine pancreas to homogeneity, The factor administered to mice intravenously at a dose of 20 pdkg b.w. decreased serum calcium by 15%. Treatment of the factor with the serine protease inhibitor, PMSF, caused a leftward shilt in the dose-response curve, showing strengthcncd activity. It also caused a decrease in serum calcium and hydroxyprolinc levels in rats, At a dose of IG ngml, the factor inhibited 15Ca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 9 publications
3
37
0
Order By: Relevance
“…The administration of purified porcine and rat caldecrin via the tail vein of mice decreased their serum calcium concentration dose-dependently and the maximum effect was attained 2-4 h post-injection with 20-100 µg (about 0.7-3.6 nmol)/kg body weight. The hypocalcemic potency of caldecrin was almost equivalent to that of porcine calcitonin (1 nmol/kg body weight, Tomomura et al [10] data not shown). The caldecrin proform (pro calderon), purified from the porcine pancreas in the presence of diisopropyl fluorophosphate, appeared to show time-and concentration-dependent chymotryptic activity following cleavage by trypsin.…”
Section: Caldecrin and Bone Metabolismmentioning
confidence: 88%
See 4 more Smart Citations
“…The administration of purified porcine and rat caldecrin via the tail vein of mice decreased their serum calcium concentration dose-dependently and the maximum effect was attained 2-4 h post-injection with 20-100 µg (about 0.7-3.6 nmol)/kg body weight. The hypocalcemic potency of caldecrin was almost equivalent to that of porcine calcitonin (1 nmol/kg body weight, Tomomura et al [10] data not shown). The caldecrin proform (pro calderon), purified from the porcine pancreas in the presence of diisopropyl fluorophosphate, appeared to show time-and concentration-dependent chymotryptic activity following cleavage by trypsin.…”
Section: Caldecrin and Bone Metabolismmentioning
confidence: 88%
“…The caldecrin-induced serum calcium decrease occurred concomitantly with a decrease in the serum concentration of hydroxyproline, which is a marker of bone resorption. This observation suggested that this serum calcium decrease may be due to the suppression of bone resorption [10] . The effects of caldecrin on osteoclast function have also been investigated; recombinant wildtype and protease activity-deficient mutant caldecrin produced concentration-dependent suppression of bone resorption in isolated rabbit mature osteoclasts [23] .…”
Section: Activity Of Caldecrinmentioning
confidence: 91%
See 3 more Smart Citations